Phytochemical, bioactivity and LC-DAD-MS/MS analyses of nam-nam (Cynometra cauliflora L.) and tampang besi (Callicarpa maingayi K. & G.) leaf extracts - Ado, Muhammad Abubakar (2016)
Current research indicates that radical oxygen species (ROS) liberated along with some other components in the body are capable of destroying cellular constituents and act as secondary messengers for some chronic diseases, such as diabetes, Alzheimer`s disease (AD), coronary heart diseases, skin disease and inflammation. Because many researchers have demonstrated that most of the drugs and additives used in the treatments of AD, diabetes, or skin diseases may result in toxic effects and causes other serious diseases, chemical and biological studies on medicinal and edible plants have been investigated to discover new active compounds. Therefore, the main objective of this study was to evaluate the effect of methanol extract and different polarity fractions of two Malaysian medicinal plants Cynometra cauliflora (nam-nam) and Callicarpa maingayi (tampang besi) leaves for their antioxidant, cholinesterase, tyrosinase and α-glucosidase inhibitory activities. In addition, the identification of the bioactive compounds from the active fractions was performed using the LC-DAD-ESIMS/MS and spectroscopic techniques. The methanolic leaf extract of C. cauliflora exhibited potent inhibition against all three enzymes and high antioxidant activity. The bioactivity was found to be concentrated in the EtOAc and n-BuOH fractions. Applying LC-DAD-ESIMS/MS to the two active fractions led to the identification of total 18 metabolites. These compounds includes isomer of procyanidin; procyanidin tetramer (139), procyanidin trimer (141) and procyanidin hexamer (149), catechin (140), isomer of taxifolin pentoside (142), vitexin (143), isovitexin (144), kaempferol hexoside (145), isomer of quercetin pentoside (146), quercetin hexoside (147), apigenin 6-C-glucose-8-C-glucose (148), kaempferol– coumaroyl-hexoside (150) and isorhamnetin hexoside (151). The phytochemical investigation of the EtOAc and n-BuOH fractions of the plant led to the isolation of four different compounds. Through a combination of spectroscopy (1D and 2D NMR) and mass spectrometry, these compounds were identified as apigenin 8-C-glucoside (143), apigenin 6-C-glucoside (144), taxifolin 3-O-arabinofuranoside (142) and acacetin 7-O-β- glucoside (152). All the compounds exhibited good to weak DPPH radical scavenging and α-glucosidase inhibitory activities and relatively moderate to weak inhibitory activity against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) when compared to positive control. Similarly for C. cauliflora, LC-DAD-ESIMS/MS was used to analyze the most bioactive fractions (EtOAc and n-BuOH) of Callicarpa maingayi. Cistanoside F (109), apigenin 6- C-glucoside-8-C-glucoside (148), β-OH-forsythoside B (132) and campneoside II (112), isocampneoside I (122), rhamnazin 3-O-rutinoside (153), forsythoside B (26), campneoside I (118), aceteoside (27), isoaceteoside (24), eukovoside (123), acacetin diglucuronide (126), apigenin 7-O-rutinoside (154), 2’-acetylacteoside (28), 2’- acetylacteoside isomer (28), acacetin 7-O-glucoronide (130), β-OH-poliumoside (114), kaempferol 3-sulfate-7-arabinopyranoside (155) and poliumoside (29), were tentatively identified based on their UV spectra and MS/MS data. All these compounds are reported in this species for the first time. Phytochemical investigations of the DCM and hexane fractions of C. maingayi were also carried out. Eight known compounds namely euscaphic acid (51), arjunic acid (156), ursolic acid (20), apigenin (131), acacetin (157), stigmasterol 3-O-β-glycopyranoside (158) and sitosterol 3-O-β-glycopyranoside (159) were isolated from the DCM fraction, while n-hexacosanoic acid (160) from the hexane fraction. Compounds 51, 156, 20, 131, 157 and 160 were isolated for the first time from the C. maingayi. Furthermore, the triterpenoid effects on AChE and α-glucosidase enzymes were also investigated. Ursolic acid (20) was found to display moderate inhibition against AChE, whereas euscaphic acid (51) and arjunic acid (156) demonstrated moderate α-glucosidase inhibitory activity. The biological activities of the crude extracts of C. cauliflora and C. maingayi and the pure compounds were in alignment with their ethno pharmacological uses. In conclusion, this study have validated the use of these plants in traditional medicinal practice and suggested that they may have potential applications in the treatment of various free radical mediated diseases.